Answer:
C.
![C=\begin{bmatrix}4&2& -7\end{bmatrix}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xkc1lrp16p7x8j92uu3yv0ovrfxr94kdym.png)
Explanation:
We are given that an equation
![\begin{bmatrix}-18&3&5\end{bmatrix}-C=\begin{bmatrix}-22&1&12\end{bmatrix}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f5vu0nt45zg828280x9fvlpcyu92s8iy52.png)
We have to find the value of C.
Let C=
![\begin{bmatrix}a&b& c\end{bmatrix}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u5rhvbvh8s4ga6kkrxjmp08z2eruuiq86e.png)
![\begin{bmatrix}-18&3&5\end{bmatrix}-\begin{bmatrix}a&b& c\end{bmatrix}=\begin{bmatrix}-22&1&12\end{bmatrix}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j5oairm8j321pi8ad554zjqmlw7ey14b5w.png)
![\begin{bmatrix}-18-a&3-b& 5-c\end{bmatrix}=\begin{bmatrix}-22&1& 12\end{bmatrix}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8k1o8r1ft4uezs53xhhaob45tqxsub4sy9.png)
When two matrix are equal then each element equals to its corresponding element.
Therefore, -18-a=-22
![a=-18+22=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aho1x66vjteis1khrhiiohyp5v9n0jsy4w.png)
![3-b=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3w95itp0gefb1wsu4je8yodhwghj8z46po.png)
![b=3-1=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kbgjn9x0ayqyfim4ym31zubnuy08ut1w81.png)
![5-c=12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lq57cnqpqkf5h6pcm5l5l1jkezszwi4mg4.png)
![c=5-12=-7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6h12azj7foe2m6ylaeq6wxnc99dqqsmgcg.png)
Substitute the values then we get
![C=\begin{bmatrix}4&2& -7\end{bmatrix}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xkc1lrp16p7x8j92uu3yv0ovrfxr94kdym.png)
Hence, option C is true.